Chronic descending colon obstruction caused by congenital band - Waseem Shater; Gulan Maree; Ali Farid Alelayan; Bardisan Gawrieh; Wajih Ali (Elsevier, 2022)
A congenital band is an infrequent abnormality. Intestinal obstruction caused by an anomalous congenital band is very rare in children. Herein, we present the case of a 6-year-old patient with intestinal obstruction due to a congenital band. The compression was at the level of the descending colon. The location of the obstruction was determined by lower GI endoscopy, but the cause of the obstruction was diagnosed intraoperatively. The band was ligated and divided without intestinal resection. To the best of our knowledge, just four cases of large bowel obstruction due to congenital bands have been reported in the literature.